Young Cuban Writers: Conversation with Jesús Jambrina (and a Brief Sample of Poets Inside and Outside the Island) (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
It was a surprise to find myself recently at a literature conference at the University of Iowa, United States, in July 2002, face to face with young Cuban intellectuals, poets, and writers. Two of them already resided here, and two others came directly from Cuba and after the Congress, they were returning to their country. I had extensive conversations with the researcher and poet Jesús Jambrina, who has been living in the United States for two years. Jambrina is 37 years old. He is a journalist graduated from the University of Havana. Between 1994 and 1998, he worked at the newspaper El Habanero, where he was the editor of the cultural page, as well as the cultural supplement Tertulia H. He then moved to the magazine Revolución y Cultura, where he served as editor-in-chief. As a literary researcher, Jambrina has published several unpublished texts by the Cuban writer Virgilio Piñera in the Cuban Gazette, for whom he is preparing a book of essays.